THE EFFECT OF COW MANURE FERTILIZER AND COCONUT WATER POC ON THE GROWTH AND PRODUCTION OF KAILAN PLANTS (Brassica oleracea Alboglabra) - Barus, Rio Rakuta; Girsang, Rosmaria; Luta, Devi Andriani (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2022)
Effect of applying cow manure and coconut water liquid organic fertilizer on the growth and production of kailan plants (Brassica oleracea Alboglabra). The aim was to determine the effect of cow manure and coconut water liquid organic fertilizer on the growth and production of kailan plants (Brassica oleracea Alboglabra) and their interactions. This experiment used a factorial Randomized Block Design (RBD) consisting of 2 factors with 16 treatment combinations and 2 blocks so that there were 32 research plots. The factors studied were the first factors in the treatment of cow manure (A) consisting of 4 levels, namely: A0 = 0 kg / plot (Control), A1 = 1 kg / plot, A2 = 2 kg / plot, A3 = 3 kg / Plots. The second factor of giving POC coconut water (K) consisted of 4 levels namely: K0 = 0 ML / L / Plot (Control), K1 = 300 ml / L / Plot, K2 = 600 ml / L/ Plot, K3 = 900 ml / L / Plot. The results showed that the effect of cow manure and coconut water liquid organic fertilizer had no significant effect on plant height (cm), number of leaves (strands), production per sample (g), and production per plot (g). The interaction between the administration of cow manure and liquid organic coconut fertilizer had no effect on plant height (cm), number of leaves (strands), production per sample (g), and production per plot (g).